“Your brain just freaks out!” – Understanding VET articulants’ transition experience using Bourdieu’s notions of habitus and field - Delly, Pamela (Journal of Academic Language and Learning, 2016)
In the broadening of pathways from the Vocational Education and Training (VET) sector to the higher education (HE) sector, a critical intersection has occurred between the transition from one education system to another. While this transition is often described as “seamless”, this is not always the case. As a result of receiving appropriate Advanced Standing, some VET students are able to articulate directly into the second year of an undergraduate degree. In by-passing the first-year program, the point of entry in Year 2 becomes a critical intersection for these students, because they are actually in their first year of university. The literature reports that these ex-VET students experience an academic skills gap, often as a result of by-passing the Year 1 program. This study foregrounds the perspectives of the students, explores this critical intersection and confirms a skills gap. The theoretical framework for the study utilises Bourdieu’s notions of field and habitus, arguing that students’ previously successful habitus is no longer appropriate in a HE setting. It seems that students need to develop a new habitus to successfully meet the academic requirements of HE. The study predominantly uses a qualitative methodology, with twelve students from a single sector university being interviewed about the strategies used to address their reported skills gap. The findings indicate students struggled to find ways to develop their academic skills, and most managed alone, despite their university providing academic support. Importantly, students reported varying degrees of eventual success in developing the academic skills needed to succeed in their HE courses.